+2.5% Improvement in generation utilizing Anti soiling modules based on DSM technology. Issue 1 (February 2021) - Verma, Rajat; Mahajan, Amresh; Pathak, Prem
Abstract: Accumulation of dust on solar modules decreases the transmittance of photovoltaic glazing, resulting in both deteriorated efficiency and daily energy losses. Actually, the soiling phenomenon in PV systems has been shown to be responsible for a medium- and long-term yield reduction of up to 16% over the first year of outdoor exposure [1].The most prominent origin of dust is driven by wind and soil particles from the ground surface. All over the planet, the properties of dust due to geological, topographical, and environmental ambiences such as relative density, particle structure, surface effects, and vapour content differ from one location to another. In the present study, an exploration of the energy gain observed by Photovoltaic modules coated with DSM Anti-Soiling coating (ASC) installed at 150 MW solar power plant in Andhra Pradesh is presented. The experiment for the analysis of the generation data started on 6 September 2018. Four different slots, one with DSM ASC and the rest with an anti-reflective coating (ARC), with equivalent DC connected load are chosen for analysis. The washing cycle was maintained at an interval of 10 days. The study shows that the modules with ASC generate +2.5% more power than the modules with ARC.